2008
DOI: 10.1097/nmd.0b013e31817762ac
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Mindfulness-Based Cognitive Therapy for Treating Insomnia in Patients With Anxiety Disorders

Abstract: The objective of this study was to examine the usefulness of a mindfulness-based cognitive therapy (MBCT) for treating insomnia symptoms in patients with anxiety disorder. Nineteen patients with anxiety disorder were assigned to an 8-week MBCT clinical trial. Participants showed significant improvement in Pittsburgh Sleep Quality Index (Z = -3.46, p = 0.00), Penn State Worry Questionnaire (Z = -3.83, p = 0.00), Ruminative Response Scale (Z = -3.83, p = 0.00), Hamilton Anxiety Rating Scale (Z = -3.73, p = 0.00)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 15 publications
2
71
0
2
Order By: Relevance
“…In women with insomnia and breast cancer, CBTI was also more effective in improving sleep, depression and anxiety symptoms than a control condition (Savard et al, 2005). Eight weeks of mindfulness-based cognitive therapy for treating insomnia symptoms also improved sleep, anxiety and depressive symptoms in patients with an anxiety disorder (Yook et al, 2008).…”
Section: The Relationship Between Sleep and Depressionmentioning
confidence: 90%
“…In women with insomnia and breast cancer, CBTI was also more effective in improving sleep, depression and anxiety symptoms than a control condition (Savard et al, 2005). Eight weeks of mindfulness-based cognitive therapy for treating insomnia symptoms also improved sleep, anxiety and depressive symptoms in patients with an anxiety disorder (Yook et al, 2008).…”
Section: The Relationship Between Sleep and Depressionmentioning
confidence: 90%
“…Benefits included reduced anxiety and emotion regulation noted in reductions in stress-cortisol (Willis, 2007;Fogarty, 2009) and a thickening of the prefrontal cortex which is associated with emotion regulation (Lazar et al, 2005;Cahn & Polich, 2006). Yook et al (2008) found through a series of questionnaires that participants reported improved sleep patterns. Improvements in attention and focus were shown in two studies (Tang et al, 2007;Jha, Krompinger, & Baime, 2007) using the ANT (Attention Network Test) designed by Rueda, Fan, McCandliss, Halparin, Gruber, Lercari & Posner, 2004).…”
Section: Benefits Of Mindfulnessmentioning
confidence: 99%
“…A range of benefits have been noted for individuals using mindfulness across various studies; many of which are confirmed by more than one study. A sample of these are included here: reduced stress and anxiety (Ludwig & Kabat-Zinn, 2008;Siegel, 2010;Willis, 2007); improved sleep patterns (Britton, Haynes, Fridel, & Bootzin, 2010;Ludwig & Kabat-Zinn, 2008;Yook, et al, 2008); improved attention (Jha, Krompinger & Baime, 2007;Semple & Lee, 2008;Tang, et al, 2007); improved mental outlook (Brown & Langer, 1990;Wenk-Sormaz 2005); learning, memory, attention, sensory processing, empathy and reduced fear (Mental Health Foundation, 2011). Although there are other research investigations that corroborate these findings across different countries, most of these studies have small sample sizes.…”
Section: What Is Mindfulness?mentioning
confidence: 99%